The Epidemiology of Auditory Dysfunction in Type 2 Diabetic Adults in Africa: 4 A Systematic Review and Meta-analysis - Fihla, Achuma (Department of Public Health and Family Medicine, 2023)
Background: There is a growing rate of diabetes related hearing loss (HL) worldwide. However, in under-developed countries, HL is still under-recognised as a complication of type 2 diabetes mellitus (T2DM). Although Africa presents a significant rise in T2DM every year, it is met with limited resources to assist its growing and ageing population. Objectives: This systematic review and meta-analysis brings awareness to diabetes-related HL in the form of reliable medical evidence measuring the prevalence of T2DM-related HL in an African population. Methods: Studies were screened using Rayyan QCRI. STATA software and the random-effects metaanalysis model was used to aggregate prevalence estimates with a 95% confidence interval. The Freeman Tukey Transformation was used to account for between study variability. The study protocol is published in PROSPERO international Register of Systematic Reviews (registration number CRD42021227801). Results: We identified a total of 99 studies, 14 duplicates were removed and 67 were excluded. After full review only five studies were included for quantitative synthesis. All the studied were crosssectional and used purposive sampling as their recruitment method. Conclusions: Findings show most participants with T2DM experienced mild HL and slight delays in objective hearing assessments. Audiometric resources and qualified Audiologists are scarce in Africa. Therefore, the available evidence does not justify the added costs needed for routine audiometric assessments for patients with T2DM. However, it does serve to recommend prioritising further research regarding risk factors associated with developing auditory disorders in people with T2DM.